Transformation of the Situ Cikaret Landscape (1901-2025):Spatial Change Analysis Based on Colonial Maps and Satellite Imagery: Spatial Change Analysis Based on Colonial Maps and Satellite Imagery - Vauzul Rahmat; Syachrul Arief; Asep Adang Supriyadi (International Journal of Technology and Education Research, 2026)
Urban water bodies such as situ play a crucial role in maintaining hydrological, ecological, and spatial balance in the region, yet their existence is increasingly threatened by urbanization, settlement expansion, and uncontrolled land conversion. Situ Cikaret is one of the water bodies in Bogor Regency experiencing high development pressure amid the growth of the Cibinong area. This study aims to analyze the landscape transformation of Situ Cikaret over the period 1901–2025 using a spatial-historical approach to identify changes in water body area, morphological changes, and surrounding land use dynamics. The research employs descriptive-quantitative methods based on spatial-temporal analysis, integrating 1901 colonial maps, multitemporal Landsat imagery, high-resolution imagery, and Geographic Information Systems. Historical maps were georeferenced using four control points, achieving a Root Mean Square Error of ±2.11 meters. Classification accuracy tests yielded an overall accuracy of 89% and a Kappa coefficient of 86.26%, indicating high data accuracy. The results show that the water body area of Situ Cikaret shrank from 49.97 hectares in 1901 to 21.08 hectares in 2025, a reduction of 57.82%. Additionally, the settlement area increased significantly from 14.78 hectares to 205.61 hectares, accompanied by morphological changes such as narrowing, loss of water body branches, and fragmentation due to landfilling activities. This study concludes that long-term urbanization is the dominant factor in the landscape transformation of Situ Cikaret and underscores the importance of protecting situ buffer zones in sustainable spatial planning.